Environmental awareness and perceived corporate social responsibility: Evidence from employees in Nigerian manufacturing firms - Animasaun, Oluyomi Olatundun; Animasaun, Sikiru Ayodeji; Kolade, Akinpelu Ayobami (Jurnal Ekonomi KIAT, 2026)
Purpose: This study explores how environmental knowledge, sensitivity, and practices influence employees perceived corporate social responsibility (PCSR) in selected consumer manufacturing firms in Lagos, Nigeria. Design/methodology/approach: The study used a cross-sectional survey, collecting data from 320 employees in Lagos's consumer goods firms via stratified random sampling. Data analysis employed PLS-SEM with SmartPLS 4 to test three hypotheses. Findings: Findings indicate environmental knowledge, practice adoption, and sensitivity positively influence employee PCSR in Lagos State's consumer manufacturing. Knowledge is the top predictor; sensitivity is significant but less impactful, challenging identity-based CSR views. PLS-predict confirms strong out-of-sample relevance, outperforming benchmarks. Limitations and Research implications: This cross-sectional study limits causal inference; the relationships are associational, not directional. The sample from Lagos-based consumer goods firms restricts generalisation to other sectors and regions in Nigeria and beyond. Practical Implications: The study offers a nuanced view of PCSR antecedents, impacting sustainability training, organizational policy, and future theory development by including dispositional, cognitive, and institutional factors. Originality/value: This study contributes to the existing body of empirical research by utilising PLS-SEM analysis.